Impact of COVID-19 lockdown on the epidemiology of soccer muscle injuries in Italian Serie A professional football players - Marotta, N.; de Sire, A.; Gimigliano, A.; Demeco, A.; Moggio, L.; Vescio, A.; Iona, T.; Ammendolia, A. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study was to evaluate the influence that COVID-19 lockdown had on the epidemiology of soccer musculoskeletal injuries during 2019/2020 Italian First Football League Serie A in professional football players. METHODS: In this retrospective study we analyzed records from media-based platform (Trasfermarkt, https://www.transfermarkt.com), describing the epidemiology of muscle injuries before and after the first COVID-19 lockdown phases in Italian professional football players. We also classified the severity of the injury as the number of missing days from participation. RESULTS: We assessed a lower prevalence of post-lockdown injuries, albeit showing a similar injury rate at 1000 game-hours (prelockdown: 16.9 [13.0-20.7], post-lockdown: 15.5 [9.9-21.1]; RR=0.92 [0.46-1.8]). All risk ratios for injury rate were not significantly different (P>0.05) between pre- and post-lockdown. CONCLUSIONS: The incidence of muscle injuries has not significantly changed after the first COVID-19 lockdown in Italian professional soccer players. Recognizing injury rates might be crucial for physician to evaluate adequate preventive measures.